2022
DOI: 10.1097/moo.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation: an effective modality for hearing restoration following vestibular schwannoma resection

Abstract: Purpose of reviewPreservation of hearing is one of the tenets of vestibular schwannoma management. In recent years, cochlear implants have been employed with increasing use in patients who have suffered profound sensorineural hearing loss due to the natural history of vestibular schwannoma or due to injury to neurovascular anatomy at time of surgical resection. Recent findingsCochlear implantation has been found to be an effective modality for hearing restoration following vestibular schwannoma. Simultaneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…The CI is considered an option in cases where there is anatomical and functional preservation of the cochlear nerve, since CI results can be superior to those of the Auditory Brainstem Implant (ABI), with less morbidity. 127 , 309 Preservation of the cochlear nerve and improved CI response have been reported for tumors of up to 2 cm. 307 , 310 , 311 The CI has been used in “wait and scan” patients with VS who showed growth stability in the last2 to 3 years 310 , 312 , 313 ; in patients undergoing microsurgery with a hearing preservation technique such as the MF, RLB, or RS that evolves with hearing loss 305 , 310 or with the TLB approach, 300 , 306 either simultaneously or sequentially; and in patients undergoing radiosurgery or radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CI is considered an option in cases where there is anatomical and functional preservation of the cochlear nerve, since CI results can be superior to those of the Auditory Brainstem Implant (ABI), with less morbidity. 127 , 309 Preservation of the cochlear nerve and improved CI response have been reported for tumors of up to 2 cm. 307 , 310 , 311 The CI has been used in “wait and scan” patients with VS who showed growth stability in the last2 to 3 years 310 , 312 , 313 ; in patients undergoing microsurgery with a hearing preservation technique such as the MF, RLB, or RS that evolves with hearing loss 305 , 310 or with the TLB approach, 300 , 306 either simultaneously or sequentially; and in patients undergoing radiosurgery or radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…The use of electrically eABR has been shown to be effective in the intraoperative assessment of cochlear nerve function after VS resection, assisting in the selection of patients who may benefit from a CI. 306 , 309 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (10)(11)(12) on vestibular schwannomas demonstrated benefit with CI placement after resection; however, these patients had tumors at the cerebellopontine angle. Literature regarding resection and CI for ILS remains limited, and studies focus on the most common subtype, intracochlear ILS (13).…”
Section: Introductionmentioning
confidence: 88%
“…Wie die CI-EBERA, ist eine ANTS-EBERA bspw. für das Monitoring bei einer Tumorresektion und geplanter Cochleaimplantation in der gleichen Sitzung geeignet, gerade wenn mangels Restgehör keine akustische BERA möglich ist [20,25,88].…”
Section: Beim Oben Angesprochenen Cochleären Monitoring Zurunclassified